فرط سكر الدم عند القبول و الاختلاطات ضمن المشفى عند مرضى احتشاء العضلة القلبية الحاد مع ارتفاع قطعة ST . (Latakia University Journal -Medical Sciences Series, 2019)
فرط سكر الدم عند القبول و الاختلاطات ضمن المشفى عند مرضى احتشاء العضلة القلبية الحاد مع ارتفاع قطعة ST . Aim of the study: This study was undertaken to assess the impact of acute hyperglycemia (Admission Hyperglycemia) on short-term outcomes during  hospitalization in patients withST elevation acute myocardial infarction (AMI). Methods: We  analyzed 148 consecutive patients admitted for STEMI to the Coronary Care Unit of in Tishreen University Hospital between 1/2/2018 and 31/1/2019 . Patients were classified according to their admission blood glucose into two groups , the first group was admission hyperglycemia (defined ≥ 200 mg/dl) , whereas the second group was without admission hyperglycemia , to assess its impact on In-hospital complications (Acute heart failure , Cardiogenic shock , Bleeding ). Results: In univariate analysis , patients with admission hyperglycemia developed acute heart failure (38.3% vs 7.9%,p=0.0001) and cardiogenic shock (28.3% vs 1.1%,p=0.0001)  more than patients without admission hyperglycemia. There wasn’t any statistical significant difference between the two groups with regard to bleeding. In multivariate analysis , Admission Hyperglycemia was an independent risk factor for acute heart failure (OR:7.2,CI95%:2.8-18.2,p=0.0001). It wasn’t an independent risk factor for either cardiogenic shock (OR:1.6,CI95%:1.1-2.3,p=0.02)   or bleeding (OR:0.7,CI95%0.06-2.8,p=0.8) . Summary: Admission hyperglycemia was an independent risk factor for Acute heart failure in STEMI patients.الهدف : إن الهدف الأساسي لهذا البحث هو دراسة تأثير فرط سكر الدم الحاد (عند القبول) لدى مرضى الاحتشاء مع ارتفاع قطعة ST على الاختلاطات قصيرة الأمد خلال فترة البقاء في المشفى. الطرق: تمت دراسة جميع مرضى الاحتشاء مع ارتفاع ST والمقبولين في وحدة العناية المشددة القلبية ضمن مشفى تشرين الجامعي بين 1/2/2018 و 31/1/2019 و البالغ عددهم 148 مريض. تم تصنيف المرضى تبعا لقيم سكر الدم عند القبول الى مجموعتين , المجموعة الأولى وهي مرضى سكر الدم المرتقع عند القبول ( أكبر أو يعادل 200ملغ/دل) و المجموعة الثانية هي مرضى سكر الدم غير المرتفع (أقل من 200 ملغ/دل) و ذلك لدراسة تأثيره على الاختلاطات الحاصلة خلال فترة الاستشفاء (قصور القلب الحاد , الصدمة القلبية , النزف الهام و المهدد للحياة) . النتائج: تبين في التحليل أحادي البيانات أن مرضى فرط سكر الدم عند القبول تطور لديهم  قصور القلب الحاد (38.3% vs 7.9%,p=0.0001) و الصدمة القلبية (28.3% vs 1.1%,p=0.0001) بشكل أشيع بالمقارنة مع مرضى سكر الدم غير المرتفع. في حين لم يلاحظ أي اختلاف ذو أهمية إحصائية بين المجموعتين فيما يتعلق بالنزف (1.6% vs 2.3%,p=0.7). التحليل متعدد البيانات أظهر أن سكر الدم المرتفع عند القبول كان عامل خطر مستقل لتطور قصور القلب الحاد  (OR:7.2,CI95%:2.8-18.2,p=0.0001) .   لكنه لم يكن عامل خطر مستقل لتطور الصدمة القلبية (OR:1.6,CI95%:1.1-2.3,p=0.02) أو النزف (OR:0.7,CI95%0.06-2.8,p=0.8) . الخلاصة: سكر الدم المرتفع عند القبول هو عامل خطر مستقل لتطور قصور القلب الحاد عند مرضى احتشاء العضلة القلبية الحاد .